2010
DOI: 10.1139/x10-024
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between field- and LiDAR-based measures of stand structural complexity

Abstract: Forest structure, as measured by the physical arrangement of trees and their crowns, is a fundamental attribute of forest ecosystems that changes as forests progress through suc;cessional stages. We examined whether LiDAR data could be used to directly assess the successional stage of forests by determining the degree to which the LiDAR data would show the same relative ranking of structural development among sites as would traditional field measurements. We sampled 94 primary and secondary sites , and 600 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(111 citation statements)
references
References 37 publications
0
111
0
Order By: Relevance
“…Earlier studies have suggested that the information in the ALS data may be condensed to a few metrics [72,73], the partitioning of which will provide a stratification corresponding closely to the structural complexity observed in the field [59,74,75]. In this study, a similar partitioning was carried out using the textural features, and the applicability of the obtained information was demonstrated by prioritizing the field plots to be measured for predicting plot V using other features.…”
Section: Unsupervised Classification Of the Forested Areamentioning
confidence: 95%
“…Earlier studies have suggested that the information in the ALS data may be condensed to a few metrics [72,73], the partitioning of which will provide a stratification corresponding closely to the structural complexity observed in the field [59,74,75]. In this study, a similar partitioning was carried out using the textural features, and the applicability of the obtained information was demonstrated by prioritizing the field plots to be measured for predicting plot V using other features.…”
Section: Unsupervised Classification Of the Forested Areamentioning
confidence: 95%
“…Previous forestry studies have assessed the accuracy of remote sensing techniques by extracting various structural metrics that play major roles in forest management and other ecological applications [9,14,23,24,39,43,55]. To assess the accuracy of the UAV-SfM point cloud in detail and to thoroughly evaluate the differences between the UAV-SfM and LiDAR point clouds, we used common plot-level structural metrics that can be easily generated from point cloud data.…”
Section: Extraction and Comparison Of Forest Structural Metricsmentioning
confidence: 99%
“…LiDAR structural metrics are strongly correlated with variation in vertical and horizontal forest structure at the stand level and hence explain the structural complexity of the overall forest canopy [9,65]. Therefore, we selected several plot-level LiDAR structural metrics described in the previous section, including mean height, canopy cover greater than 2 m, and surface area ratio, to determine the influence of stand structure on the RMSD of canopy height.…”
Section: Identification Of Factors That Affect the Performance Of Uavmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that forest inventory variables can be measured and modeled accurately (and precisely) from LiDAR height and density metrics [1][2][3]. These include critical parameters, such as species identification [4], mean diameter at breast height (DBH) [5,6], stand and canopy structural complexity [7,8], forest succession [8], fractional cover [9], leaf area index (LAI) [9,10], crown closure [11], timber volume [6,12,13] and biomass [14][15][16][17]. Estimation of many forest inventory variables using LiDAR data is now moving beyond the research realm and into the operational forum [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%